Otomatisasi Pengawasan Penggunaan Masker Pada Siswa Yayasan Pendidikan Shafiyyatul Amaliyyah (YPSA) - Reyhan Achmad Rizal; Marlince Novita Karoseri Nababan; Despaleri Perangin-Angin (Smart Education, 2021)
In preparing for face-to-face meetings, the Shafiyyatul Amaliyah Education Foundation (YPSA) requires supervision in applying the use of masks in the school envi-ronment. There are two main problems that exist at YPSA, namely supervising students at YPSA it is difficult for one supervisor to do and the size of the pages at YPSA is difficult to reach every student because students at YPSA vary from kindergarten, elementary, junior high and high school. The solution offered by the PKMS team at Universitas Prima Indonesia is to build an automation system with a door opening and closing model and a warning alarm at the entrance to the school environment. The initial implementation of this activity was carried out on August 16, 2021 to conduct interviews with YPSA part-ners in order to obtain a model of the automation tool for monitoring the use of masks in accordance with the YPSA environment. Every student is protected from the transmission of the Covid-19 virus.